MERIT40 facilitates BRCA1 localization and DNA damage repair - Feng, Lin (Cold Spring Harbor Laboratory Press, 2009)
The product of breast cancer susceptibility gene 1, BRCA1, plays pivotal roles in the maintenance of genomic integrity. Mounting evidence indicates that BRCA1 associates with many proteins or protein complexes to regulate diverse processes important for the cellular response to DNA damage. One of these complexes, which mediates the accumulation of BRCA1 at sites of DNA breaks, involves the ubiquitin-binding motif (UIM)-containing protein RAP80, a coiled-coil domain protein CCDC98/Abraxas, and a deubiquitinating enzyme BRCC36. Here we describe the characterization of a novel component of this complex, MERIT40 (Mediator of Rap80 Interactions and Targeting 40 kd), which together with an adaptor protein BRE/BRCC45, enforces the BRCA1-dependent DNA damage response. MERIT40 is assembled into this RAP80/CCDC98-containing complex via its direct interaction with BRE/BRCC45. Importantly, MERIT40 regulates BRCA1 retention at DNA breaks and checkpoint function primarily via a role in maintaining the stability of BRE and this five-subunit protein complex at sites of DNA damage. Together, our study reveals that a stable complex containing MERIT40 acts early in DNA damage response and regulates damage-dependent BRCA1 localization.